Making Out in Chinese : Revised Edition (Mandarin Chinese Phrasebook). - Ray (Tuttle Publishing, 2013)
Making Out in Chinese is a fun, accessible and thorough Mandarin Chinese phrase book and guide to the Mandarin Chinese language as it's really spoken. Wo xiang geng liao jie ni. You kong ma?-(I want to know more about you. Do you have free time?) Answer this correctly in Chinese and you may be going on a date. Incorrectly, and you could be hurting someone's feelings or getting a slap! Mandarin Chinese classes, textbooks and Mandarin phrasebooks tend to spend a lot of time rehearsing for the same fictitious scenarios but chances are while in China you will spend a lot more time trying to make.